Gold: Cardiff University, United Kingdom 4 - 6 July 2011 - Hutchings, Graham (Faraday discussions, 2011)
No abstract available
Gesehen am 15.09.2022
Keywords: Konferenzschrift; Kongress; Katalysator; Heterogene Katalyse; Nanopartikel; Gold